Perspectives on the quality of basic education in Ibero-America: Spain and Colombia insights (2018)
Basic education is responsible for consolidating the structures of the education system. Many countries in the world have made significant efforts in terms of coverage and, to a greater extent, for the purpose of improving quality. However, more and more often the quality of education is the protagonist in this field debates, especially from social and economic development approaches. This research article shows the relation of these policies, in Spain and Colombia, as a means to recognize common and divergent elements. This text is part of an extensive research work entitled “Quality policies of primary education in Colombia (1994 - 2015)” whose methodological framework is the qualitative paradigm. The results reveal that the quality of education is a concept associated with learning goals, and from the competency model is established what a student should know and know how to do after completing his schooling, this process must be evaluated internally and externally.